Webcharts – A Web-based Charting Library for Custom Interactive Data Visualization. Issue 1 (19th July 2016) - Bryant, Nathan; Wildfire, Jeremy
Webcharts is a JavaScript library built on top of D3.js that creates reusable, flexible, interactive charts that are highly customizable. Webcharts provides a method for creating commonly-used charts, including bar charts, scatterplots, and timelines, through a simple configuration scheme. Charts created with Webcharts allow users to dynamically manipulate chart data, appearance, and behavior both through callback functions and input elements that are tied to chart objects. This approach allows users to create reusable charts that range from simple static graphics to complex interactive data exploration tools with custom user interfaces, all using the same library.